STUDY OF DEVICES AND METHODS FOR MEASURING THE MAGNETIC AND MAGNETIC-OPTICAL PROPERTIES OF RARE EARTH IONS (British Journal of Global Ecology and Sustainable Development, 2025)
This article analyzes the main equipment and methods used to measure the magnetic and magnetic-optical properties of rare earth ions. Magnetic properties and magnetic-optical effects provide in-depth information about the study of physical properties, electronic and magnetic structure of materials. Detailed information about the devices used in the research - magnetometers, spectroscopy devices and optical measuring devices - is discussed, their advantages and limitations are discussed. These methods are the basis for the widespread application of rare earth-based materials in research and industry.